Estimasi Cadangan Batubara PT. Pancaran Surya Abadi, Kecamatan Muara Badak-Anggana, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Andres Melbaral; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2023)
Abstract. PT. Pancaran Surya Abadi is a private company engaged in coal mining, this company performs coal mining using the open pit mining method. Based on the Decree of the Minister of Energy and Mineral Resources No. 1827 K of 2018, concerning Guidelines for the Implementation of Good Mining Rules, states that every mining company is required to report a plan for managing the remaining reserves in its territory as part of conservation, and with the increase in coal prices, the company plans to expand the mining area in the northern PIT with a PIT limit from SR 1:4 to SR 1:5 by conducting PIT design and coal reserve estimation. From the PIT design, the calculation results of the area that will be used as a potential PIT is approximately 50 Ha. Calculation of reserves at PT. Pancaran Surya Abadi uses a comparison of the Conventional method (Triangle) with the Geostatistical method (Ordinary Kriging). From the results of the estimated reserves, the coal in PT. Radiant Surya Abadi if calculated using the Triangle Method, the total reserve value is 3,719,204.50 tons, while if it is calculated using the Ordinary Kriging Method, the total reserve value is 4,079,375.50. The conclusion of this research is that the calculation method that is considered correct is the Ordinary Kriging Method because it tends to produce block estimates that are more evenly distributed or less varied than the actual levels.